Case report on Tuberous Sclerosis - Shrestha, Sushma; Shrestha, Sabina; Ojha, Anil Raj (Journal of Kathmandu Medical College, 2014)
Tuberous Sclerosis Complex is a rare genetic disorder inherited in autosomal dominant fashion. It is a multisystem disorder involving brain, skin, kidneys, heart, eyes and lungs which becomes apparent only in late childhood, limiting the usefulness of early diagnosis in infancy. Here, we report a case of an 11 year male child with tuberous sclerosis. DOI: http://dx.doi.org/10.3126/jkmc.v2i4.11798 Journal of Kathmandu Medical College Vol. 2, No. 4, Issue 6, Oct.-Dec., 2013 Page : 208-210